IMPLEMENTASI MATA PELAJARAN PROJECT KREATIF DAN KEWIRAUSAHAAN PADA JURUSAN DKV SMK NEGERI 1 MERANGIN UNTUK MEMBANGUN KEMANDIRIAN KARIER (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Creative Project and Entrepreneurship (PKK) subject in the Visual Communication Design (DKV) Department of SMK Negeri 1 Merangin as an effort to build students’ career independence. The PKK subject serves as a platform for developing creativity, innovation, and entrepreneurial skills through various applied projects that are relevant to the creative industry. This research uses a descriptive qualitative method to present the planning process, the implementation of learning activities, and the outcomes achieved by students through design-based projects. The results of the study show that the implementation of PKK in the DKV Department is conducted through various activities such as creating visual content, designing creative products, developing brand identity, and producing digital promotional media. Teachers, department coordinators, and students play active roles in each stage—from generating ideas and managing production, to simple marketing practices and product evaluation. Through project-based learning, students gain hands-on experience in developing creative products, working collaboratively, managing time, and identifying business opportunities within the design industry. Positive impacts of the implementation include improved managerial abilities, increased creativity and confidence in producing original work, and stronger motivation to build independent careers as designers or entrepreneurs in the creative sector. Additionally, these project activities help strengthen students’ independence, responsibility, and entrepreneurial mindset as essential competencies for entering the workforce and exploring future business opportunities.